2018
DOI: 10.1111/sode.12339
|View full text |Cite
|
Sign up to set email alerts
|

Couple interaction and child social competence: The role of parenting and attachment

Abstract: The current study examined the association between positive couple interaction and child social competence as mediated through positive parenting and parent–child attachment security. Prospective, longitudinal data came from 209 mothers, fathers, and their biological child. Information regarding observed positive couple interaction, observed positive parenting, and parent–child attachment security were assessed when the child was 2–4 years old, and child social competence was assessed at 5 years old. Mothers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 69 publications
(98 reference statements)
1
16
0
Order By: Relevance
“…This supports earlier findings which demonstrated associations in positivity (Neppl et al 2015) and positive parenting between mothers and father using the APIM (Daniel et al 2016;Neppl et al 2015Neppl et al , 2018. However, we were not able to support interdependent associations between maternal or (paternal) positivity and their partner's positive parenting.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This supports earlier findings which demonstrated associations in positivity (Neppl et al 2015) and positive parenting between mothers and father using the APIM (Daniel et al 2016;Neppl et al 2015Neppl et al , 2018. However, we were not able to support interdependent associations between maternal or (paternal) positivity and their partner's positive parenting.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, according to Kenny and colleagues, a mother and father from the same family are not independent, thus a research model should consider the family unit and the dynamic interdependent relationship between mother and father (Cook and Kenny 2005;Kenny and Ledermann 2010;Ledermann et al 2011). Indeed, research has shown significant associations between mother and father positivity and mother and father positive parenting (Neppl et al 2015(Neppl et al , 2018, as well as the interdependent lagged associations between mother and father warm parenting using Actor-Partner Interdependent models (Daniel et al 2016). Results demonstrate that a mother (or father) who showed higher positivity and positive parenting styles were more likely to have a partner who also showed positivity and positive parenting (Neppl et al 2015(Neppl et al , 2018.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the media use of children and mothers, dysfunctional parent–child interactions have been shown to be associated with behavioral difficulties in young children [8,22]. Furthermore, infrequent interactions between parents and children could be linked to lower prosocial behavior in children [8], whereas positive parenting and parent–child attachment have been shown to be related to more social competence [23].…”
Section: Introductionmentioning
confidence: 99%
“…The attachment fostered by the caregivers (fathers) and their children is a provision that will be brought to their social world through social interaction. This will also be an ability for them to adapt with their social environment (Neppl, et al, 2019). Good relationship with caregivers will make a child have secure attachment and develop good interaction with other people, which leads them to have a good social adjustment (Fatmawati, 2020).…”
Section: Description Of Permissivementioning
confidence: 99%